Comparative study regarding the stability of a proximal ulnar stump with or without distal oblique bundle reconstruction during the Sauvé‒Kapandji procedure: a finite-element analysis - Yin, Shanqing; Zhang, Chenxi; Huang, Yaopeng; Pan, Jiadong; Wang, Xin; Liu, Xiaodong (Frontiers in Bioengineering and Biotechnology, 2025)
BackgroundThe most common postoperative complication of the Sauvé‒Kapandji (S-K) procedure is proximal ulnar stump instability. The distal oblique bundle (DOB) is a stable tissue used to stabilize the distal radioulnar joint. This study created finite-element models of the distal oblique bundle (DOB) to determine its effect on the proximal ulnar stump instability encountered during the Sauvé‒Kapandji procedure.PurposeWe hypothesized that a proximal ulnar stump with distal oblique bundle reconstruction would provide greater stability than a proximal ulnar stump without distal oblique bundle reconstruction.MethodsDetailed CT imaging data acquired from a pathological specimen of the wrist joint were imported into a finite-element analysis software package, and the regions of interest, including bone, cartilage, ligaments and tendons, were extracted to create a 3-dimensional model. The volar/dorsal and medial/lateral displacements of the proximal ulnar stump and the stress changes exhibited by the bone and distal oblique bundle tendon were measured with and without DOB reconstruction under 60° pronation, neutrality, and 60° supination.ResultsWhen utilizing DOB reconstruction, the displacement of the radius relative to the proximal ulna stump was approximately 17.89 mm in the neutral position. The bone stress values corresponding to the neutral position, 60° pronation and 60° pronation were 1.01, 18.32 and 14.69 MPa, respectively. The stress peaks of the DOB tendon structure corresponding to the neutral position, 60° pronation and 60° pronation were 0.07 MPa, 2.21 and 1.55 MPa, respectively. Without DOB reconstruction, the displacement of the radius relative to the proximal ulna stump was approximately 18.05 mm in the neutral position. Under 60° pronation and 60° supination, the displacement values were approximately 14.62 mm and 16.89 mm, respectively. The peak bone stress values corresponding to the neutral position, 60° pronation and 60° supination were 1.02, 18.29 MPa and 14.41 MPa, respectively. The stress peaks of the tendon structure corresponding to the neutral position, 60° pronation and 60° pronation were 0.03, 0.87 and 0.85 MPa, respectively.ConclusionDOB reconstruction is capable of improving the stability of the proximal ulnar stump during the Sauvé–Kapandji procedure.